IMPLEMENTASI DATA LOGGER MENGGUNAKAN SD CARD PADA PEMBANGKIT LISTRIK TENAGA SURYA DI TAMBAK UDANG BANJARASRI KECAMATAN TANGGULANGIN KABUPATEN SIDOARJO JAWA TIMUR - alim aktual iman qowiyah, alim; Solikin, Akhmad; Wijaya, Wildan Surya (Universitas Islam Balitar Blitar, 2025)
Solar Power Plants (PLTS) are an environmentally friendly alternative source of renewable energy, especially in tropical regions like Indonesia. PLTS offers an ideal solution to support electrification in areas that are difficult to reach by the power grid, such as the shrimp pond in Banjarasri, Tanggulangin, Sidoarjo. This pond, covering approximately 2 hectares, utilizes PLTS to meet energy needs, particularly for nighttime lighting. However, one of the main challenges in operating PLTS is the limited real-time performance monitoring system. Failure to detect a drop in panel efficiency, damage to the solar charge controller, or battery overload can lead to energy loss and high maintenance costs. This study examines the implementation of a PLTS monitoring system using an SD Card-based data logger as an affordable and independent solution without relying on internet connectivity. The system has been tested to record parameters such as battery voltage, charging current, load current, and load voltage. Measurement results show that deviations between SD Card readings, Serial Monitor, and manual measuring instruments are very small (±0.01–0.3), demonstrating the system’s accuracy and consistency. With the support of an RTC module, data timestamping also runs synchronously and stably. In conclusion, integrating PLTS with an SD Card-based monitoring system proves effective in supporting efficient and sustainable shrimp pond operations. This technology enables early detection of system disturbances, faster technical decision-making, and long-term operational cost savings.